ANALYSIS OF THE IMPORTANCE OF DIGITAL MARKETING IN ENTREPRENEURIAL BUSINESS: THE CASE OF THE REPUBLIC OF SERBIA - PANOVSKI, Boban; STOJANOVIĆ, Miloš; POPOVIĆ, Milica; CVETKOVIĆ, Filip; STANKOVIĆ, Nemanja (Journal of process management and new technologies, 2025)
Nowadays, entrepreneurship plays an important role in the development of economy in the Republic of Serbia. However, in order for entrepreneurial ideas to really come to life and become successful, it is necessary for entrepreneurs to have an effective marketing strategy that will help them gain recognition and attract customers. Precisely in this context, digital marketing has imposed itself as an unavoidable factor in modern entrepreneurship. The modern era of digital transformation has changed the way entrepreneurs approach marketing. Today, digital marketing is one of the most effective ways to gain recognition, increase sales and attract new customers. Entrepreneurs in the Republic of Serbia increasingly recognize the importance of digital marketing, and apply different digital marketing strategies to improve their business. The goal of this paper is to investigate the importance of applying digital marketing in entrepreneurship in the era of the new digital economy. Through the analysis that was conducted, it was determined that entrepreneurs in the Republic of Serbia attach great importance to digital marketing. It was also concluded that those entrepreneurs who have been in business longer and have a larger number of employees, at the same time attach more importance to digital marketing channels.
Keywords: Digital marketing; entrepreneurs; entrepreneurship